PENINGKATAN KEMAMPUAN KINERJA GURU DALAM MENYUSUN STRATEGI PEMBELAJARAN MELALUI KEGIATAN WORKSHOP (PENELITIAN TINDAKAN SEKOLAH DI SD NEGERI 2 BIES KABUPATEN ACEH TENGAH T.P. 2013/2014 - Heriandi Effendi (JURNAL TEMATIK, 2014)
Teacher Performance Improvement In The Ability Of Learning Through Setting Strategies Workshop Activities (Measures Research In SDN 2 Bies District Central Aceh Academic Year 2013/2014) This study aims to: (1) to determine the workshop can improve the ability of teachers in preparing instructional strategies; (2) to determine the role of the workshop in enhancing the ability of teachers to teach in Elementary School 2 Bies Central Aceh District; (3) to determine any obstacles encountered in the implementation of the workshop to enhance the ability of teachers to implement learning strategies in Elementary School 2 Bies Central Aceh District; (4) to assess the efforts made by the head of school at SDN 2 Bies Central Aceh district in improving the ability of teachers to implement learning strategies. This study is an action research (action research) that aims to improve teacher performance through a learning strategy workshops at SDN 2 Bies. Actions to be taken is the preparation of the workshop learning strategy. The selected action research is emancipatory kind. Emancipatory type is considered the most appropriate because the research is done to solve the problems on their own research work areas based on daily experience. The subject of this study are teachers at SDN 2 Bies Central Aceh district totaling 16 people, consisting of: 10 the male teachers and 6 female teachers. While the object of study is the performance of the teacher in preparing learning strategies.